Reforma al código de la niñez y adolescencia, respecto de las pensiones alimenticias y su justificación - Palma Gálvez, Rodrigo Mauricio (2017)
The Constitution of the Republic of Ecuador, Article 44 establishes the rights of children and adolescents, also it notes that the State, Society and Family promoted as a priority the integral development of children and adolescents and will ensure the full exercise of their rights prevail over those of the people; integral development is understood as the process of growth, maturation and deployment of their intellect and their capabilities, potential and aspirations in a family, school, social and community effectiveness and safety for the satisfaction of their social, emotional needs environment, emotional and cultural. So that currently children enjoy the best interests principle and belong to a group of priority attention for its vulnerability to other people, so our law protects children with fundamental rights which are also expressed in the Code children and adolescents, which in Article 45 states that children and adolescents shall enjoy the common rights of human beings, in addition to the specifics of your age and state guarantee life, including the care and protection from conception, They will also have the right to physical and mental integrity, holistic health, education, freedom and receive information about their parents or absent, except family members would be detrimental to their welfare. From the above we see that children and adolescents should enjoy a quality life so that their development is complete, at all stages of the child's life in a family, social and community effective environment for it and recognizing the fundamental right of children in the Ecuador has been raised alimony them have visibly improved in an effort to ensure food for children and adolescents; however, have been violated and are violating basic rights of loan fed, likewise it has violated a universal principle is proportionality and reciprocity; that is, a large percentage of pensions are excessively high in relation to expenses demanded by the care of the child. In the social sphere has been observed as the rights of minors are violated by stop those who have tenure, usually mothers, as children do not receive education or the care they need according to their age; however, they are receiving expensive pension by their parents. In addition, according to data provided by the National Institute of Statistics and Census INEC, the basic family basket for 2016 was set at 683.00, just as I determine that a family with 1.6 income earners with basic wages could acquire the basket it consists of food and non-food items necessary for the maintenance of a month in a household of 4 members, so that to get more alimony even unified workers' basic salary, the person should be required to justify the costs incurred for the sole purpose of resources actually received for alimony, they have invested only in the minor for support to have a full life and quality; so it is very important the introduction of a legal reform in the Code for Children and Adolescents criminalizing the justification of expenses for alimony.